Successful Treatment of Pulmonary Arterial Hypertension in Systemic Sclerosis with Anticentriole Antibody - Yusho Ishii; Hiroshi Fujii; Koichiro Sugimura; Tsuyoshi Shirai; Yosuke Hoshi; Yoko Fujita; Yuko Shirota; Tomonori Ishii; Hiroaki Shimokawa; Hideo Harigae (Case Reports in Rheumatology)
Systemic sclerosis (SSc) is characterized by skin sclerosis and multiple organ damages which may cause mortality and is usually accompanied with several specific autoantibodies, each of which is associated with characteristic complications. Among them, anticentriole antibody is recently reported to be highly associated with SSc-associated pulmonary arterial hypertension (SSc-PAH). In general, several vasodilators are used as therapeutic drugs for SSc-PAH, whereas immunosuppressive therapies are not. Here, we report the case of a 62-year-old female with anticentriole antibody-positive SSc-PAH treated with immunosuppressants and vasodilators. She presented with two-year exertional dyspnea and was diagnosed with PAH and SSc owing to the centriole staining pattern and other symptoms without digital sclerosis. Oral vasodilators were initially administered but were not sufficiently effective on dyspnea. Immunosuppressants such as prednisolone and cyclophosphamide were started. Both of them improved mean pulmonary arterial pressure and 6-minute walk distance, and the anticentriole antibody also disappeared. In this case, SSc-PAH with anticentriole antibody was properly diagnosed and immunosuppressants and vasodilators improved the hemodynamics of PAH with anticentriole antibody and stably maintained it and, in addition, reduced the titer of anticentriole antibody. This indicates that anticentriole antibody might represent a good responsive group to therapies among subgroups of patients with SSc-PAH.